Exploring the Therapeutic Potential of Mimosa pudica L. in Indonesian Traditional Medicine - Kristiana, Lusi; Lestari, Weny; Supriadi, Mery Budiarti (Althea Medical Journal, 2025)
Background: Traditional medicine and traditional healers have a long history of treating diseases in Indonesia. One of the plants that has been used by traditional healers (battra) is Mimosa pudica L. (MP), which is easily found throughout Indonesia. This study aimed to explore the therapeutic potential of traditional herbal medicine containing MP by battra in Indonesia. Methods: This study used a descriptive method using secondary data from the Research on Medicinal Plants and Herbal Medicine (Riset tumbuhan obat dan jamu/RISTOJA), which was conducted in 2012, 2015 and 2017 by the Ministry of Health Indonesia. This study analyzed the utility of MP from 106 concoctions made by 90 battras, from 80 ethnic groups in 23 provinces of Indonesia. Concoctions were categorised based on the parts used, and the herbs’ composition, including preparation and administration. Results: Mimosa pudica L. (MP) in 106 concoctions divided into 48 single-plant uses and 70 multi-plants uses, to treat 38 diseases. The most concoctions were for skin diseases (10 concoctions), followed by rheumatism and gout (9), tumor/cancer and cough (8), haemorrhoids (7), diabetes (6), low back pain (4), and jaundice (4). The most common administration was orally (65.1%). The leaves were the most widely used in herbal medicine, by drinking after being boiled in water.Conclusions: This study provides information on the use of Mimosa pudica L. (MP) concoctions by battra from various ethnic groups and provinces in Indonesia. MP has a variety of pharmacological activities that are consistent with its use in traditional medicine, even potentially addressing age-related diseases such as antidiabetic, anticholesterol, and antihyperlipidemic. Further studies are needed to evaluate the effectiveness and efficiency of multi-ingredient herbal medicines, as well as its preparation and administration in relation to hygiene.